PELATIHAN KEARSIPAN BAGI TENAGA PENDIDIK DAN TENAGA KEPENDIDIKAN DI SDN SUKARESMI 04, KABUPATEN BEKASI - Niantoro Sutrisno; Herry Syafrial; Faridah Faridah; Ria Estiana; Djumat Purnomo (JURNAL ABDIMAS PLJ, 2021)
The role of archives in every organization or institution is very important, one of which is as a memory center. Organizations will find it difficult to prove something if the organization does not have good records. In principle, archives have several important roles where the aim is to help smooth organizational activities in planning organizational policies. The school is one of the organizations that has many archives, for example invitations both official and committee, diplomas, student report cards, school accreditation files, teacher administration, school administration, championship administration owned by school residents, and others. These archives will be very unfortunate if not managed properly, because it is important for the progress and success of the school. The problems that occurred at SDN Sukaresmi 04 Bekasi Regency related to archives were due to the lack of awareness of educators and education staff in the importance of managing archives, especially regarding the types of documents and about how to archive school documents. The series of service activities are carried out in two stages. The first stage is observation where universities make visits to SDN Sukaresmi 04, Bekasi Regency to identify problems that occur during the documentation process of administrative activities at the school. The second stage is to carry out activities to provide material regarding archiving documents in schools for educators and education staff.Keyword: archiving documents, schools